2018
DOI: 10.1097/fpc.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in candidate genes are not associated with increased vincristine-related peripheral neuropathy in Arab children treated for acute childhood leukemia

Abstract: This study presents the first pharmacogenetic analysis of vincristine-related peripheral neuropathy in children with ALL in an Arab country. We have shown that genetic polymorphisms in candidate genes are not associated with peripheral neuropathy secondary to chronic therapy with high-dose vincristine (2 mg/m) during the continuation phase. Concerning CEP72, our results are in line with the findings from the St Jude cohort of children treated for ALL with higher vincristine doses during chronic treatment. Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…Mutations in CEP72 and CYP3A5 have been most extensively studied as factors possibly influencing the development of vincristine-induced neuropathy. Studies have demonstrated that SNPs that reduce CEP72 expression may lead to the development of neuropathy in patients on vincristine [29,30], although subsequent studies were unable to consistently reproduce this finding [31,32]. Vincristine is primarily metabolized by CYP3A4 and 3A5.…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…Mutations in CEP72 and CYP3A5 have been most extensively studied as factors possibly influencing the development of vincristine-induced neuropathy. Studies have demonstrated that SNPs that reduce CEP72 expression may lead to the development of neuropathy in patients on vincristine [29,30], although subsequent studies were unable to consistently reproduce this finding [31,32]. Vincristine is primarily metabolized by CYP3A4 and 3A5.…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…McClain et al (2016) also found no significance with polymorphisms in the CEP72 gene, while Wright et al (2019) showed that CEP72 (rs924607), SLC547 (rs1013940) (choline transporter), and Alpha Tocopherol Transfer Protein (TTPA, binding to vitamin E) (rs1050436) were significant associated with a higher risk of developing neuropathy. No association was found by Zgheib et al (2018) between VIPN and CEP72 (rs924607), Ewing's tumor-associated antigen 1 (ETAA1) (rs17032980) and Melatonin Receptor 1B (MTNR1B) (rs12786200). Li et al (2019) investigated two independent cohorts and used a meta-analysis to assess the association between multiple SNPs and VIPN.…”
Section: Pharmacodynamics Stability Of Microtubules and Neurotoxicitmentioning
confidence: 99%
“…A significant higher risk of developing neurotoxicity grades 1 to 4 during vincristine treatment was found for rs3740066 and rs12826 in the ABCC2 gene. Zgheib et al. (2018) assessed the association between grade II or higher VIPN and ABCB1 (rs1045642), ABCB1 (rs1128503) and ABCC2 (rs717620).…”
Section: Role Of Pharmacogenetic Variations In Chemotherapeutic Relatmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 , 161 Results were however not replicated in two other studies. 162 , 163 More recently whole-exome sequencing of DNA from 240 European children with ALL revealed an association between four variants in four genes ( BAHD1 rs3803357, MRPL47 rs10513762, SYNE2 rs2781377 , and CDH2 rs1944294 ) with VINC-related neuropathy, 66 however these results were not yet validated in other populations.…”
Section: Evidence For the Individualization Of Treatment Regimensmentioning
confidence: 99%